Zbirke mineralov, rud in kamnin Marjana Dolenca - Jeršek, Miha (Scopolia, 2011)
Marjan Dolenc, with BSc in geology as his educational qualification, upgraded his rich career of economic geologist and professional searcher of ores and ore minerals with a comprehensive collection of minerals, ores and rocks. He assembled them in six different collections. In 2011, he donated the central four systematic and at the same time thematic collections to the Slovenian Museum of Natural History. These are: a systematic collection of minerals, a collection of rock minerals, a collection of mineral and ore deposits, and a systematic petrographic collection and geological phenomena. Each of them is furnished with a short presentation and a table with data on individual specimens or a transcript of the manual inventory book, supplemented and standardised in a form suitable for print. Each mineral, ore or rock specimen and its inventory number is accompanied by details of the finder, the manner in which found, and locality of each specimen.
Keywords: Dolenc, Marjan, 1919-; mineralogy; ores; mineralogija; rocks; rude; rudeness; kamnine; systematics; karbonatiti; collections; carbonatites; sistematika; zbirka